2006
DOI: 10.1097/01.dad.0000164604.56650.26
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Antibiotic-Induced Eruptions Associated With Epstein Barr Virus Infection and Showing Kikuchi-Fujimoto Disease-Like Histology

Abstract: The antibiotic-induced eruption of infectious mononucleosis is a well-known clinical phenomenon. Latent viral infection with herpesviridae (eg, human herpes virus 6 (HHV-6) and Epstein-Barr virus (EBV)) is suspected to play a role in the drug hypersensitivity syndrome. The cutaneous pathologic findings have not been reported in the former, and are infrequently reported in the latter entity. Herein, we describe the biopsy findings of a cefprozil-induced rash in infectious mononucleosis and a minocycline-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The presence of HHV-6 was not assessed in this study [82]. HHV-6 reactivation was observed in two patients with sulfasalazine severe hypersensitivity [83].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HHV-6 was not assessed in this study [82]. HHV-6 reactivation was observed in two patients with sulfasalazine severe hypersensitivity [83].…”
Section: Discussionmentioning
confidence: 99%
“…80,90,91 The rash usually remits and is not associated with recurrence, even with subsequent administration of the same antibiotic on other occasions (unless the patient shows hypersensitivity to the drug or atopic symptoms). 93 Carlson et al 94 reported an adverse drug reaction in 2 patients with EBV infection (one with IM and the other with chronic active EBV) in which the morphologic changes were similar to the ones observed in cutaneous involvement by the Kikuchi disease (KD). Rarer accompanying manifestations are edema of the lips and eyelids, diarrhea, or arthralgias.…”
Section: Drug Eruptions and Ebvmentioning
confidence: 79%
“…Similar, but less extensive deposition of nuclear debris associated with PM has been described in adverse antibiotic eruptions occurring during acute and latent EBV infection. 19 In this latter scenario, the antibiotic is believed to act as an antigen stimulating T-lymphocyte proliferation that secondarily potentiates active or triggers transition from latent to active EBV infection.…”
Section: Discussionmentioning
confidence: 99%